Silymarin protects the liver from α-naphthylisothiocyanate-induced cholestasis by modulating the expression of genes involved in bile acid homeostasis: Anti-cholestatic effect of silymarin - Sohail, Imran; Malkani, Naila; Tahir, Nimra; Khalil, Ateeb; Attar, Rukset; Mumtaz, Sidra (Cellular and Molecular Biology, 2022)
Cholestasis is characterized by impaired bile flow which results in inflammation, cirrhosis, and ultimately liver failure. The current study is aimed to evaluate the anti-cholestatic effect of silymarin against α-naphthylisothiocyanate (ANIT) induced cholestasis. Mice were gavaged with various doses of silymarin or ursodeoxycholic acid (UDCA) for 19 days. Then they were challenged with α-naphthylisothiocyanate (ANIT) and after 48 hours the animals were sacrificed to obtain blood and liver sections. Serum levels of bilirubin, aspartate transaminase (AST), alanine transaminase (ALP), and liver histology were analyzed. mRNA expression of selected transporters (Bile salt export pump (BSEP) and sodium taurocholate cotransporting polypeptide (NTCP)) and proteins (farnesoid x receptor (FXR) and Cytochrome P450 Family 7 Subfamily A Member 1 (Cyp7a1)) involved in bile acids biosynthesis, excretion and uptake were also evaluated by quantitative PCR. The results indicated that the serum levels of bilirubin, AST, and ALP were significantly higher in a cholestatic model group as compared to an untreated control group. However, in silymarin groups, the serum level of these parameters is significantly lower than in a cholestatic model group. Liver histology also showed that silymarin prevents ANIT-induced hepatic injury. mRNA expression of FXR, BSEP, and NTCP was downregulated and expression of Cyp7a1 was upregulated in a cholestatic model group as compared to an untreated control group. However, in silymarin treatment groups, the expression of FXR, BSEP and NTCP was upregulated and the expression of Cyp7a1 was downregulated as compared to the cholestatic model group. In conclusion, silymarin could alleviate hepatic injury by modulating the expression of genes involved in bile acid homeostasis.